Wpływ języka włoskiego na obecny kształt języka molizańskich Chorwatów - Feruga, Krzysztof (Slavia Centralis, 2020)
Italian influence on the contemporary language of Molise Croats Neighbouring nations and their languages cannot avoid mutual contacts, including communication contacts, which lead to different interferences in their own and the other language systems. There are huge numbers of lexical language borrowings in the common speech of Molise Croats that depend on the invention of the interlocutors. They try to adjust their lexis to both languages when they communicate with elder people, whereas they use Italian when they talk to their peers or to young people. This paper shows how Molise Croats cope with new vocabulary connected with development of technology, culture and civilization.